A Study On The Sorption Isotherm And Shelf Life of Intermediate-Mosture Banana (IMB) - Suyitno Suyitno (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1989)
Water vapour sorption isotherm of intermediate moisture banana (IMB) was studied by means of Saturated salt solution technique at 22.2C. The desoprtion and adsorption isotherms of IMB were sigmoid shape and indicate a hysteresis loop.The self life of IMB based on the hardening phenomena in polyethylene pouch stored at 22.2C and RH 50% and 73% ferpouch was investigated. In a 73% RH chamber, IMB in the package theoretically would never harden to a critical point.